L’apport de la lecture de textes sources dans l’écriture des textes documentaires par des élèves de 2e année du primaire - Gagnon, Renée; Ziarko, Hélène (Canadian Journal of Applied Linguistics, 2008)
This article presents the results of a pretest-postest study which examined the impact of different instructional procedures on the ability of Grade 2 elementary children in experimental and control groups to produce written expository texts involving a comparison. Referring to texts the children had read to prepare them for the writing activity, instruction variously focused on drawing their attention to the rhetorical structure and linguistic features typically associated with the targeted genre. The results reported herein pertain to how the children used their readings as a resource for the informational content of the texts they produced during the post-test. Overall, semantic analysis of the informational content reveals no significant difference between experimental and control groups. However, children in the experimental group significantly outperformed the latter in terms of their ability to produce texts which, from a rhetorical perspective, better reflected the features associated with texts involving comparisons.